Ni-Fe metals in the type 3 ordinary chondrites - Nagahara, Hiroko (1982)
P(論文) Metals in four type 3 ordinary chondrites (ALH-77015,-77278,-77299 and -77304) are classified into four types based on their occurrence; those within chondrules, those on the surface of chondrules, those in the matrix and those forming chondrules. Metals within chondrules have higher Co contents than those on the surface or in the matrix, indicating that they would have cystallized from the liquid at higher temperatures. Modal ratios of discrete kamacite, discrete taenite and coexisting grains are different from those in the chondrites of higher petrologic types, and they are considered not to have been heated above about 500℃. Most metals in the type 3 ordinary chondrites show compositional zoning due to decreasing temperature; however, zoning in kamacite is more conspicuous than in the chondrites of higher petrologic types. According to diffusion coefficients of Ni in kamacite and taenite, metals in the type 3 ordinary chondrites should have cooled 2 orders of magnitude more rapidly below 500℃ than those in the chondrites of higher petrologic types. This difference would be a constraint for the estimation of the parental body of the ordinary chondrites. departmental bulletin paper